PENGARUH KOMPOSISI KOTORAN JANGKRIK, AYAM DAN KAMBING DENGAN TANAH REGOSOL TERHADAP PERTUMBUHAN SEMAI SENGON LAUT - , ORLANDO VALENTIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Seedling growth media requirements require physical-chemical properties of good. Physically, media should have high porosity so that the growth of seedling roots will not have problems. One of the good media, the organic materials that has decomposed completely because it can increase the porosity of media. While chemically media must be able to provide the nutrients necessary for the growth and development of the seedling. Currently increasing number of farmers cricket, chicken and goat feces throwing away waste. These impurities could be expected to improve soil physical and chemical properties that can be used as a media mixing of plant in order to get a good quality seedling. This research was aims to determine the mixing of ratio cricket dirt with regosol soils, chicken dirt with regosol soils and goat dirt with regosol soils on the growth of Seedling sengon sea until the age of three months. The method used, that is with measurement of growth parameters including height, diameter and rate of survival at Seedling sengon sea. This research use CRD design (Compelety Randomize Design) by treatment with three types of dirt, that is dirt cricket, chicken and goat mixed with regosol soils comparison, that is 1:1, 1:2, 1: 3 and control (without dirt). The results showed the survival rate sea sengon seedling highest on the composition of goat and soil mixing of regosol with a ratio of 1:3, of 100%. For high mean of sea sengon seedling was highest in the composition of goat and soil mixing of regosol with a ratio of 1:1, that is 1,23 cm. For diameter mean of sea sengon seedling was highest in the composition of goat and soil mixing of regosol with a ratio of 1:2, that is 0,012 cm.